Iron-containing N-doped carbon electrocatalysts for the cogeneration of hydroxylamine and electricity in a H2–NO fuel cell. Issue 6 (4th November 2015) - Daems, Nick; Sheng, Xia; Alvarez-Gallego, Yolanda; Vankelecom, Ivo F. J.; Pescarmona, Paolo P.
Abstract : Iron-containing N-doped carbon materials are active electrocatalysts for the cogeneration of hydroxylamine and electricity in a H2 –NO fuel cell, which is a promising alternative to the present industrial synthesis. Abstract : Iron-containing N-doped carbon materials were investigated as electrocatalysts for the cogeneration of hydroxylamine (NH2 OH) and electricity in a H2 –NO fuel cell. This electrochemical route for the production of hydroxylamine is a greener alternative to the present industrial synthesis, because it allows converting the energy released during the reaction into electricity. The studied electrocatalysts were prepared by pyrolysis of composites of activated carbon and polyaniline (PANI) incorporating Fe sites (Fe-PANI-AC). Characterisation with a combination of techniques (FT-IR and Raman spectroscopy, XRD, N2 -physisorption, XPS and ToF-SIMS) showed that the materials exhibit promising features as electrocatalysts for the NO reduction reaction, as they contain the desired isolated FeN x C y sites and have a relatively high degree of graphitisation, which grants good electrical conductivity. The performance of the Fe-PANI-AC electrocatalysts was investigated by means of linear sweep voltammetry (LSV) in a half cell setup and by chronoamperometry in a H2 –NO fuel cell setup and compared to that of a reference electrocatalyst consisting of iron phthalocyanine supported on activated carbon (FePc/AC). The Fe-PANI-AC electrocatalysts led to higher current density than FePc/AC under all studied conditions. At low NO concentration in the feed, FePc/AC displayed higher selectivity towards hydroxylamine, whereas the Fe-PANI-AC electrocatalysts were superior at higher NO concentration ( i.e. at the industrially more relevant conditions), both in terms of production rate and of selectivity towards hydroxylamine. Moreover, the Fe-PANI-AC electrocatalysts exhibited high stability under the fuel cell operating conditions. In summary, Fe-PANI-ACs displayed very promising electrocatalytic performance in the reduction of NO to hydroxylamine and offered the additional advantage of being less expensive compared to the reference FePc/AC electrocatalyst or to a benchmark noble-metal-based electrocatalyst as Pt/AC.